Discordant biochemical parameters of acromegaly remission do not influence the prevalence or aggressiveness of metabolic comorbidities: a single-center study - Romanisio, Martina; Pitino, Rosa; Ferrero, Alice; Pizzolitto, Francesca; Costelli, Samuele; Antoniotti, Valentina; Marzullo, Paolo; Aimaretti, Gianluca; Prodam, Flavia; Caputo, Marina (Frontiers in Endocrinology, 2023)
Purpose The discrepancy between the biomarkers of disease’s activity in acromegalic patients (GH and IGF-1) is almost frequent representing a challenge for the development of comorbidities in the long term. The aim of this study was to evaluate the prevalence and severity of metabolic comorbidities (diabetes, hypertension, and dyslipidemia) in surgically treated acromegalic patients with disease control and discordant GH and/or IGF-1 levels compared with those with concordant values. Patients and methods Retrospective monocentric observational study on acromegalic surgically treated patients with biochemical remission (group A) or mild discordant GH or IGF-1 levels (group B). Metabolic complications and medical therapy were assessed at diagnosis and at the last follow-up visit. Severity of the disease was set for drug titration or shift to another molecule or more than before. Results There were 18 patients that met the inclusion criteria [group A: nine patients; group B: nine patients, follow-up 7 years (IQR 5.0;11.25)]. The prevalence of female patients was significantly higher in the remission group compared with the discordant group (p < 0.02). Considering metabolic complications, at the last follow-up, 61.1% was affected by hypertension, 33.3% by diabetes, and 61.1% by dyslipidemia, without differences between groups. Drug characteristics (dose, shift, number) during the follow-up did not differ significantly between groups. Conclusion Metabolic complications, mainly dyslipidemia, are frequent in cured acromegalic patients, but GH/IGF-1 discrepancy does not seem to represent a risk factor for their presence or persistence. More extended studies are needed to confirm our results in a long-term period.